The Impact of Embargo Policies on Access and Satisfaction Levels of Users of The Digital Library Collection at UIN Sunan Ampel Surabaya - Nashir, Abdun (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2026)
This study aims to analyse the effect of embargo policies on access and satisfaction levels among users of the digital library collection at the UIN Sunan Ampel Surabaya Library. Referring to the rector's decree number 1308, the embargo was implemented in order to maintain originality for the purposes of publication and patent rights. This study uses a quantitative method with a survey approach, with a research population of 500 people and a sample of 84 people. Data collection was carried out through questionnaires distributed to library users involved. Data analysis was carried out using simple linear regression analysis techniques to determine the extent to which the embargo policy affects the level of access and use of digital collections in the library. The results of the study show that (1) the embargo policy implemented at the UIN Sunan Ampel Surabaya Library has a significant impact on access to digital collections. This means that the better users' perceptions of the embargo policy, the higher their access to available digital collections. (2) The embargo policy also affects the level of user satisfaction in accessing digital collections; the implementation of a clear and transparent embargo policy increases user satisfaction. (3) The impact of the embargo policy is felt by all academic community users, including students, lecturers, and the general public.